Evaluation of maternal urinary tract infection as a potential risk factor for neonatal urinary tract infection. - Nasrin Khalesi; Nastaran Khosravi; Ali Jalali; Leila Amini (Tehran University of Medical Sciences, 2014)
Objective: To assess the relationship between maternal UTI during pregnancy and neonatal UTI. Materials and methods:This cross-sectional study included eighty neonates referred to Ali-e-Asghar Hospital, Tehran, Iran, in 2011. The participants were divided into the study (with diagnosis of UTI; n = 40) and the control (without this type of infection; n = 40) groups. The mothers were asked about the history of UTI during pregnancy, and if the response was positive, the trimester in which UTI had occurred. Urinalysis and urine culture were carried out for all neonates.Overall, 14.9% of neonates had mothers with a positive history of UTI during their pregnancy (4.4%, 6.1%, and 4.4% during the 1(st), 2(nd), and 3(rd) trimesters, respectively). A significant relationship was detected between the occurrence of UTI in neonates and maternal UTI, so that the overall prevalence of UTI among neonates of affected mothers was significantly higher than that observed among non-infected mothers (30.0% versus 6.8%; p = 0.001). Maternal UTI resulted in 5.9-fold increased risk of neonatal UTI. In UTI group, the most common bacterial etiologies of UTI were Escherichia coli (65.9%), followed by Klebsiella (14.6%) and Staphylococci (9.8%). Conclusion: Our findings confirmed the association between the history of UTI in mother and occurrence of UTI in neonate, emphasizing to pay more attention for assessing and managing UTI in neonates in order to reduce the related complications.